(untitled) (Research, Society and Development, 2021)
The use of live food has been recommended in the larval stage of several species of fish, providing better survival and growth results when compared to those obtained with artificial diets. This study aims to evaluate the biomass and protein content of Daphnia magna submitted to three diets: Diet A (Scenedesmus acuminatus) at a concentration of 1.5x107 cells/mL per individual, diet B (cattle manure) at 6.5g/L, and diet C at the same diets and concentration as in diets A and B for a period of 21 days. The experiment was repeated three times, totaling 63 days of study with a completely randomized design, with three replicates in each treatment. The experimental unit consisted of polyethylene containers with 20L, containing 10 D. magna neonates. Every two days, temperature, pH, dissolved oxygen and saturation were measured. At the end of the experimental period, nutrient quantification of the culture water and diets (phosphorus, nitrate, ammoniacal nitrogen, total nitrogen, and organic nitrogen), determination of the final biomass and protein content of the individuals were performed. Diet C provided a higher mean biomass value, followed by diet A and B, with values ​​of 344.12 g, 157.71 g and 81.93 g, respectively. The D. magna fed with diet B had a higher protein content, with 2.56%, followed by those fed diets C and A, with 2.17 and 1.32%, respectively. At the end of the experiment, it was found that the organisms fed diet C had a larger reproduction rate when compared to the other diets.